Computational Fluid Dynamics modeling of the trace elements dispersion and comparison with measurements in a street canyon with balconies in the city of Patras, Greece. (15th February 2020) - Karkoulias, V.A.; Marazioti, P.E.; Georgiou, D.P.; Maraziotis, E.A.
Abstract: A sampling campaign was conducted within the downtown area of the city of Patras, Greece (Maizonos St.) in a relatively deep city street canyon (of an aspect ratio equal to h/w = 2.33) over the period between November 15, 2004 and February 28, 2005. Aerosol particle samples which were collected at various heights ( z/h = 0.10, 0.57, 0.75 and 1.00) on the windward side of a multi-floor apartment building followed by an overall mass and species composition analysis. The results explicitly showed that the mass concentration of the aerosol particles and most trace elements were greater at the street and roof levels compared to the canyon intermediary levels (the 16- and 21-m level data). Thus, it was deduced that the vertical profiles of the traffic related pollutant concentrations don't follow the expected exponential reduction function. The experimental results were confirmed by a Computational Fluid Dynamics (CFD) simulation carried out for the same street canyon geometry by employing the ANSYS-FLUENT commercial suite. In addition, the above CFD results showed that local wind flow and pollutant transport were influenced strongly by the flow vortices generated by the facade roughness elements (balconies). Following a validation process for the ANSYS-FLUENT suite the study was extended to street canyon geometries of different aspect ratios ( h/w) and building facade roughness elements (balconies) that generated the corresponding wind flow structures and pollutant transport behaviors. Emphasis was focuses on the formation (number, strength and size) of wind vortices inside the canyon. It was concluded that the vertical gradients of the aerosol particle and trace element concentrations may be attributed to this complex wind flow field. In conclusion, the analysis illuminated the need for high-resolution grids near the source for primary pollutants in urban settings. Highlights: Correction and improvement of air pollution forecasting and measurement models. Risk assessment of pollutants from road traffic in the urban population. Increasing tools for managing urban pollution to protect residents. A contribution to environmental urban planning.